JURNAL KESEHATAN HUBUNGAN FREKUENSI PEMBERIAN SUSU FORMULA DENGAN KESULITAN MAKAN PADA BALITA DI DESA PAGUTAN KECAMATAN MANYARAN KABUPATEN WONOGIRI - Aminatul Fatayati S.ST.,MPH (STIKES DUTAGAMA KLATEN, 2021)
Background : Malnutrition was a nutritional status based on the body weight index for age(BB/U) which was the equivalent of the term underweight. Indonesia is one of the developingcountries with complex nutritional problems, based on (RISKESDAS, 2018), in Indonesia it was17.7%. in Wonogiri Regency reached 3.0%, while for Manyaran District the prevalence ofmalnutrition cases was 6 under five or 0.37%. Malnutrition can occur due to the consumption ofless nutrients, the lack of nutrient intake was strongly influenced by the mother's knowledgeabout complementary feeding, behavior towards the type of complementary fed, and the mother'slifestyle in provided fast food complementary foods. Formula Milk was a fast food that is high inprotein so that children will found it difficult to ate main meals.Objective: To determine the relationship between the frequency of gave formula milk with feddifficulties in toddlers in Pagutan Village, Manyaran District, Wonogiri Regency.Research Methods: This research was quantitative used non-experimental methods with anobservational research design. The sampling method used is non-probability sampling techniquewith a sample of 43 respondents. Data analysis was toke used the Chi square test.Results: based on the analysis test carried out indicated by the value of p = 0.027 <0.05. there isa relationship between the frequency of formula fed with fed difficulties.Conclusion: the frequency of gave formula milk can cause fed difficulties in toddlers in PagutanVillage, Manyaran District, Wonogiri Regency.